Treatment and persistence with oral anticoagulants among newly diagnosed patients with non-valvular atrial fibrillation: a retrospective observational study in a US commercially insured and Medicare Advantage population. Issue 6 (30th June 2018) - Willey, Vincent; Franchino-Elder, Jessica; Fu, An-Chen; Wang, Cheng; Sander, Stephen; Tan, Hiangkiat; Kraft, Elizabeth; Jain, Rahul
Abstract : Objectives: With the approval of new non-vitamin K antagonist oral anticoagulants for stroke prevention in non-valvular atrial fibrillation (NVAF), it is anticipated that their introduction may change NVAF treatment patterns; however, there is limited supporting real-world evidence. This study investigated guideline-recommended oral anticoagulation (OAC) treatment and persistence in newly diagnosed patients with NVAF to understand demographic and clinical characteristics. Design: Retrospective observational administrative claims study in the USA. Setting: Patients with NVAF with ≥1 pharmacy claim for OAC (warfarin, dabigatran, rivaroxaban or apixaban) and no atrial fibrillation diagnosis within 12 months prior to the first claim were identified in the HealthCore Integrated Research Database between 1 November 2010 and 30 November 2013. Participants: 45 092 patients with NVAF were included. Outcomes: The proportion of OAC-treated patients was stratified by CHADS2 score. Treatment persistence was measured from OAC initiation to discontinuation, end of eligibility or end of study period (30 November 2014), whichever occurred first. Results: Almost half of the patients (41.1%) received an OAC. The proportion treated differed slightly in baseline stroke risk (CHADS2 <2: 39.8%; CHADS2 =2 or 3: 42.4%; and CHADS2 >3: 40.3%: p<0.001). Treated patients were slightly younger (70±12.2 vs 71±14.3 years; p<0.001), more likely male (59.7% vs 52.5%; p<0.001) and had a slightly elevated stroke risk (CHADS2 : 2.03±1.3 vs 1.98±1.4; p<0.001) and a lower bleeding risk (HEMORR2 HAGES: 2.55±1.8 vs 2.80±1.9; p<0.001) relative to untreated patients. Overall, patients with higher CHADS2 scores had higher HEMORR2 HAGES scores. The mean follow-up was 2.25 years (2.25±0.85) and 72.7% of patients discontinued OACs; nearly 25% within 3 months and 55% within 12 months. The mean time to discontinuation was 255±249 days. Conclusions: The proportion of patients with NVAF who received OAC treatment was lower than previously reported and differed slightly by stroke risk. Patients with an elevated stroke risk had a higher bleeding risk, suggesting that clinicians may incorporate both in the treatment decision.